Smart Solar Powered Hydroponic Close-Loop Low-Land Condition (Smart-HCO2) - Jumaat, Siti Amely; Ismail, Muhammad Nafis; Jamil, Ansar; Mohamad Nor, Ahmad Fateh; Salimin, Suriana; Abdul Rahman, Muhammad Shafiq (Multidisciplinary Applied Research and Innovation, 2025)
The hydroponic system is one of the modern agricultural techniques that is popular due to its easy control, space efficiency, and water-saving benefits. However, manually administering fertilizer in large quantities can be burdensome for farmers. To address this, the project introduces an automated hydroponic system with a sensor-based fertilizer concentration detection mechanism connected to a nutrient reservoir. Water continuously flows to the plant roots throughout the day. The entire system operates on solar energy, utilizing a solar panel 405W with 12V 200Ah lead-acid battery and a 1200W inverter with MPPT. Testing was conducted with cherry tomatoes, bell peppers, and Japanese cucumbers from August 2023 until June 2024. The plants were adjusting the fertilizer concentration to 700ppm in the first two weeks and increased it to 1200ppm in 3rd and 4th weeks, the plants began flowering early—within 30 days of being transferred to the hydroponic system. This approach not only saves electricity but also optimizes fertilizer usage and reduces plant maintenance time. In conclusion, this project contributes to sustainable agriculture by harnessing green energy technology while minimizing fertilizer and water consumption and reducing environmental pollution.